Window Design Strategies for Environmentally Friendly and Energy Efficient Patient Rooms: A Case Study in the Belgian Context. (June 2019) - Eisazadeh, N; Allacker, K; De Troyer, F
Abstract: With the increasing awareness of sustainable design "operational energy use", "life cycle environmental impact" and "comfort" are becoming key considerations for design decisions. These three aspects are usually not explored in an integrated way in the early design stage. During this stage however, most far-reaching design decisions are made and the greatest potential to achieve sustainable building designs in a cost-efficient way exists. Hence energy efficiency, environmental performance and comfort should be considered as a fundamental part of early design stage decisions. This paper investigates the influence of various patient room design options on the energy cost, life cycle environmental impact and daylighting. The design parameters investigated are the room geometry, type of glazing and WWR (Window-to-Wall Ratio). The analysis is performed for a case study in Belgium, more specifically a patient room in a hospital design. The existing design is taken as a baseline scenario and via parametric analysis, the influence of alternative design strategies is analysed. Based on the comparative analysis, the paper discusses potential design strategies that allow for energy efficient and environmentally-friendly patient rooms that fulfil comfort requirements for patients.